1996
DOI: 10.1109/63.506118
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and design of a multiple feedback loop control strategy for single-phase voltage-source UPS inverters

Abstract: This paper presents the analysis and design of a multiple feedback loop control scheme for single-phase voltagesource uninterruptihle power supply (UPS) inverters with an L-C filter. The control scheme is based on sensing the current in the capacitor of the load filter and using it in an inner feedback loop. An outer voltage feedback loop is also incorporated to ensure that the load voltage is sinusoidal and well regulated. A general statespace averaged model of the UPS system is first derived and used to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
105
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(108 citation statements)
references
References 9 publications
0
105
0
3
Order By: Relevance
“…Although the response of an inverter is faster with a single feedback loop, a multiple feedback loop is more advantageous in shutting off overcurrent and improving the transient response of inductor [1][2][3][4][5][6][7][8]. The multiple feedback loop control method is widely used by researchers because of the ease of implementation and good performance [9,10]. A multiple feedback loop controller is typically composed of voltage control in the outer loop and current control in the inner loop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the response of an inverter is faster with a single feedback loop, a multiple feedback loop is more advantageous in shutting off overcurrent and improving the transient response of inductor [1][2][3][4][5][6][7][8]. The multiple feedback loop control method is widely used by researchers because of the ease of implementation and good performance [9,10]. A multiple feedback loop controller is typically composed of voltage control in the outer loop and current control in the inner loop.…”
Section: Introductionmentioning
confidence: 99%
“…A multiple feedback loop controller is typically composed of voltage control in the outer loop and current control in the inner loop. Numerous control strategies such as PI [9,10], predictive control [11,12], deadbeat control [13,14], and repetitive control [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] are used for controlling the outer and inner loops. However, these controllers have a problem to make a design of controller optimally, which should be considered on both outer loop and inner loop.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation circuit is consists of three phase source, controlled rectifier, inverter, SPWM controller, filter, multilevel inner loop controller [9], [10], [11] and three phase nonlinear load. The simulation is done by Matlab /Simulink environment.…”
Section: Simulationmentioning
confidence: 99%
“…Switching techniques such as unipolar and bipolar were used in article [1], for analyzing the harmonics in the inverter circuit with filter. Article [2] explains how inverter can be interface with photovoltaic panels to ac network, and also paper discusses how current harmonics in inverter can be eliminated by unipolar and bipolar switching techniques. After simulation result paper concluded that for low value of switching frequency, bipolar switching techniques provide less current distraction but it is not suitable for high switching frequency.…”
Section: Introductionmentioning
confidence: 99%